2013
DOI: 10.1016/j.molonc.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant signalling by protein kinase CK2 in imatinib‐resistant chronic myeloid leukaemia cells: Biochemical evidence and therapeutic perspectives

Abstract: Chronic myeloid leukaemia (CML) is driven by the fusion protein Bcr-Abl, a constitutively active tyrosine kinase playing a crucial role in initiation and maintenance of CML phenotype. Despite the great efficacy of the Bcr-Abl-specific inhibitor imatinib, resistance to this drug is recognized as a major problem in CML treatment. We found that in LAMA84 cells, characterized by imatinib-resistance caused by BCR-ABL1 gene amplification, the pro-survival protein kinase CK2 is up-regulated as compared to the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 42 publications
1
44
2
Order By: Relevance
“…The equivalent effects on vemurafenib responses of kinase-intact and kinase-inactive CK2␣ that we observed argue that the kinase activity is not important in the vemurafenib response of BRAF mutant melanoma, but it is certainly possible that other genetic differences may also affect the relative roles of catalytic activity versus protein-protein interactions. Our study differs from work by Borgo et al (16), who found a kinase-dependent role of CK2 in imatinib-resistant chronic myeloid leukemia. These differences may reflect the divergent genetic and epigenetic contexts of BCR-ABL mutant chronic myeloid leukemia versus BRAF mutant melanomas.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The equivalent effects on vemurafenib responses of kinase-intact and kinase-inactive CK2␣ that we observed argue that the kinase activity is not important in the vemurafenib response of BRAF mutant melanoma, but it is certainly possible that other genetic differences may also affect the relative roles of catalytic activity versus protein-protein interactions. Our study differs from work by Borgo et al (16), who found a kinase-dependent role of CK2 in imatinib-resistant chronic myeloid leukemia. These differences may reflect the divergent genetic and epigenetic contexts of BCR-ABL mutant chronic myeloid leukemia versus BRAF mutant melanomas.…”
Section: Discussioncontrasting
confidence: 99%
“…In cells depleted of CK2␣, gemcitabine induced MKK4/JNK signaling, resulting in cell death (15). Furthermore, CK2 displayed elevated protein expression and activity in chronic myeloid leukemia cells that are resistant to the small molecule kinase inhibitor imatinib (16). Either reduction of CK2␣ expression or pharmacological inhibition of CK2␣ kinase activity restored imatinib sensitivity, possibly through suppressing Akt activity (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35] Importantly, it was clearly demonstrated that BCR-ABL/CKII complex plays an essential role in the regulation of imatinib resistance. 36 To verify whether PTEN tail phosphorylation is regulated by BCR-ABL, the BCR-ABL inhibitor imatinib and/or the casein kinase inhibitor TBB were utilized in BCR-ABL expressing NIH3T3 cells and PTEN phosphorylation levels were assessed by western immunoblot, upon normalization of PTEN levels. As shown in Figure 2A, the association Imatinib and TBB revert PTEN tail phosphorylation induced by BCR-ABL.…”
Section: Cd34mentioning
confidence: 99%
“…2C). 32,34,36 Next, to determine whether BCR-ABL mediates PTEN phosphorylation by Casein Kinase II, we performed an in vitro kinase assay with purified ABL protein and with PTEN and CKII immunoprecipitated proteins, as described in Material and Methods. As shown in Figure 2D, the presence of ABL increases PTEN phosphorylation induced by CKII.…”
Section: Cd34mentioning
confidence: 99%